Implementasi Metode Scrum pada Perancangan Sistem Informasi Tata Usaha SMP Negeri 1 Tanarighu Berbasis Web - Friska Priskila Wanda; Gergorius Kopong Pati; Alexander Adis (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The increasingly rapid use of information technology is now an important need for various sectors of people's lives. The various conveniences offered, such as speed and accuracy in data processing, make information technology difficult to separate from daily life, especially in the world of education. At SMP Negeri 1 Tanarighu, the processing of student payment data is still carried out conventionally, which risks causing errors in data processing. Therefore, it is very necessary to have an information system that can process student payment data centrally and integrated. This information system is expected to reduce human error and increase efficiency in the administrative process. The Scrum method, known for its ability to manage projects with limited time and dynamic needs, is very appropriate to apply in the design of this information system. By using the Scrum method, the process of creating information systems can be carried out faster and more flexibly, adjusting to evolving needs, and ensuring more accurate and efficient data management at SMP Negeri 1 Tanarighu.